Photovoltaic system's power converter - LI YANQUAN (2016)
The utility model provides a photovoltaic system's power converter relates to solar energy power generation, track controller and gate driver including solar battery array, direct current / direct current transducer, voltage electric current sensor, maximum power. The utility model discloses a power converter acquires the output and the output voltage slewing rate of direct current / direct current transducer 2, tracks the controller through maximum power and drives the gate drive ware to with the modulation of disturbance observation to direct current / direct current transducer responsibility cycle, reach impedance match's purpose, make the solar cell display can to work at maximum power point, can be too can the battery be maximum power and export and carry out energy -saving control to solar photovoltaic system. 本实用新型提出种光伏系统的电源转换器，涉及太阳能发电，包括太阳能电池阵列、直流/直流转换器、电压电流感测器、最大功率追踪控制器及闸极驱动器。本实用新型的电源转换器，获取直流/直流转换器2的输出功率以及输出电压信号变化率，通过最大功率追踪控制器来驱动栅极驱动器，并以扰动观察法对直流/直流转换器责任周期的调变，达到阻抗匹配的目的，使得太阳能电池陈列能够工作在最大功率点，可将太能能电池做最大功率